Implementasi Penempatan Sentra Wisuta Kuliner Menggunakan Multidimensional Scalling : Studi Kasusdi Kota Madya Surabaya : Studi Kasusdi Kota Madya Surabaya - Ghalib, Royyan (Jurnal Cakrawala Informasi, 2024)
Optimal placement of culinary tourism centers is very important to increase the attractiveness of tourist destinations and support local economic growth. This study aims to implement the Multidimensional Scaling (MDS) method in determining the most appropriate location for culinary tourism centers in a city. The Multidimensional Scaling approach is used to map visitor and stakeholder perceptions of various location determinants, such as accessibility, supporting facilities, market potential, and environmental characteristics. Data collected from surveys and field observations are processed to identify dominant perception and preference patterns, and determine the ideal coordinates for the location of culinary centers. The results of mapping using multidimensional scaling are Group 1 consisting of SWK Babat Jerawat, SWK Balas Klumprik, SWK Bratang Binangun, SWK Dharmahusada, SWK Embong Sawo, SWK Indrapura, SWK Kapas Krampung, SWK Penjaringan Sari, SWK Rmi, SWK Tanah Merah and SWK Tandes. Group 2 consists of SWK Convention Hall, SWK Ketabang, SWK Klampis Ngasem, SWK Krembangan, SWK Sukomanggal, SWK Terminal Manukan, SWK Urip Sumoharjo, SWK Wiyung, and SWK Wonorejo. Group 3 consists of SWK Deles Mer, SWK Dharmawangsa, SWK Gayungan, SWK Gunung Anyar, SWK Kandangan, SWK Lidah Kulon, SWK Mulyorejo, SWK Sememi, and SWK Semolowaru. And finally Group 4 consists of SWK Bentul, SWK Dukung Menanggal, SWK Jajar Tunggal, SWK Karah, SWK Kembang Kuning, SWK Manukan Lor, SWK Pegirian, SWK Putro Agung, SWK Siwalan Kerto and SWK Taman Prestasi. Group 1 is very suitable as a tourist reference because it is close to hotels, tourist attractions and mosques, group 2 is suitable as a tourist center or new business because it is far from various strategic locations. Group 3 is suitable for local residents because it is close to housing and mosques. For group 4, it is suitable for people around who pass by the area around group 4.